89.4k views
4 votes
Which equation is equivalent to the formula below?
Y = A ( X - H) ^2 + K

Which equation is equivalent to the formula below? Y = A ( X - H) ^2 + K-example-1

1 Answer

1 vote

Answer:

B. a = y - k/(x-h)²

Explanation:

Given the expression y = a (x-h)² + k

First make a the subject of the formula

Subtract k from both sides

y = a (x-h)² + k

y- k = a (x-h)² + k - k

y - k = a (x-h)²

Divide through by (x-h)²

y - k/(x-h)² = a

a = y - k/(x-h)²

Hence option B is correct

User Asdfkjasdfjk
by
5.9k points